2015
DOI: 10.1016/j.juro.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Histological Analysis of the Kidney Tumor-Parenchyma Interface

Abstract: Most renal cancers have an intrarenal pseudocapsule. Partial nephrectomy excision adjacent to the tumor edge appears to be histologically safe. Because 18% of cancers lacked a discernible intrarenal pseudocapsule and 25% of pT1a cancers showed intrarenal pseudocapsule invasion, extreme care is needed to avoid positive margins during enucleative partial nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 23 publications
4
49
2
6
Order By: Relevance
“…11,12,24 Additionally, higher rates penetrating pseudocapsule disease in RCC may be seen in patients with of higher Fuhrman grade tumors and more advanced TNM stage. 6,[8][9][10]23 In the current study, i-Cap scores of 1, 2 and 3 were assigned to 79 (24%), 176 (54%) and 72 (22%) tumors, respectively amongst the entire cohort. Tumors scored as i-Cap 2 made up largest percentage of the cohort.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…11,12,24 Additionally, higher rates penetrating pseudocapsule disease in RCC may be seen in patients with of higher Fuhrman grade tumors and more advanced TNM stage. 6,[8][9][10]23 In the current study, i-Cap scores of 1, 2 and 3 were assigned to 79 (24%), 176 (54%) and 72 (22%) tumors, respectively amongst the entire cohort. Tumors scored as i-Cap 2 made up largest percentage of the cohort.…”
Section: Discussionmentioning
confidence: 97%
“…The integrity of the pseudocapsule may vary greatly depending on the histological features of the tumor it surrounds. 11,23,24 Previous literature has demonstrated that tumor subtype may be predictive of pseudocapsule characteristics. 11,12,24 Additionally, higher rates penetrating pseudocapsule disease in RCC may be seen in patients with of higher Fuhrman grade tumors and more advanced TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…To better inform the anatomic and oncologic propriety of enucleative PN, histologic examination of the tumor-parenchyma interface was performed on 124 nephrectomy specimens [11]. Some 82% of malignant tumors had an intrarenal pseudocapsule (PC) with a median thickness of 0.6 mm.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Также нами отмечено, что опухоль имела плохо выраженную псевдокапсулу, поэтому при выполнении атипичной энуклеорезекции у пациентов было возможно оставление участка опу-холевой ткани в области дна резекции, который мог служить причиной развития местного рецидива опу-холи. По данным мировых исследований, псевдокап-сула имеет ся у 82 % опухолей паренхимы почки, тол-щина данной структуры опухоли в среднем составляет до 0,6 мм [13].…”
Section: Fig 1 the 1 St Patient's Data: а б -3d Modeling Of Patholunclassified
“…Однако, по данным R. A. Azhar и соавт., на основа-нии исследования данных 123 пациентов, подвергну-тых резекции почки, инвазия псевдокапсулы была установлена в 28 % случаев у больных с опухолью по-чки со стадией Т1а, при этом у всех больных морфо-логически был подтвержден отрицательный хирурги-ческий край [13].…”
Section: Fig 1 the 1 St Patient's Data: а б -3d Modeling Of Patholunclassified